Safe conduct of traffic through highway construction and maintenance zones. (Research results digest (National Cooperative Highway Research Program), 1978)
"A staff digest of the progress and status of NCHRP Project 20-5, "Synthesis of information related to highway problems," for which the Transportation Research Board is the agency conducting the research."